Protein Kinases and Phosphatases of the Plastid and Their Potential Role in Starch Metabolism - White-Gloria, Chris; Johnson, Jayde J.; Marritt, Kayla; Kataya, Amr; Vahab, Ahmad; Moorhead, Greg B. (Frontiers in Plant Science, 2018)
Phospho-proteomic studies have confirmed that phosphorylation is a common mechanism to regulate protein function in the chloroplast, including the enzymes of starch metabolism. In addition to the photosynthetic machinery protein kinases (STN7 and STN8) and their cognate protein phosphatases PPH1 (TAP38) and PBCP, multiple other protein kinases and phosphatases have now been localized to the chloroplast. Here, we build a framework for understanding protein kinases and phosphatases, their regulation, and potential roles in starch metabolism. We also catalog mapped phosphorylation sites on proteins of chloroplast starch metabolism to illustrate the potential and mostly unknown roles of protein phosphorylation in the regulation of starch biology.